2018
DOI: 10.1177/1558944718810882
|View full text |Cite
|
Sign up to set email alerts
|

Smoking Increases Postoperative Complications After Distal Radius Fracture Fixation: A Review of 417 Patients From a Level 1 Trauma Center

Abstract: Background: Unstable distal radius fractures that undergo surgical stabilization have varying complication rates in the literature. Smoking is known to affect bone healing and implant fixation rates but has never been definitively shown to affect postoperative outcomes of surgically managed distal radius fractures. Methods: A retrospective review was performed of patients with surgically treated distal radius fractures at a Level 1 Trauma Center who had at least 6 weeks of follow-up over a 5-year period. Chart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 32 publications
2
25
0
Order By: Relevance
“…Despite frequent reports on smoking as a risk factor for osteoporosis, fragility fractures, and associated post-surgical complication (e.g., delayed/impaired healing, infections, or revision surgeries) [3,4,5,6,7,8,9], little is known about the underlying mechanisms. Consequently, handling of smokers during and after musculoskeletal surgeries remains a huge challenge, as no specific treatment strategies exist for these patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite frequent reports on smoking as a risk factor for osteoporosis, fragility fractures, and associated post-surgical complication (e.g., delayed/impaired healing, infections, or revision surgeries) [3,4,5,6,7,8,9], little is known about the underlying mechanisms. Consequently, handling of smokers during and after musculoskeletal surgeries remains a huge challenge, as no specific treatment strategies exist for these patients.…”
Section: Discussionmentioning
confidence: 99%
“…An extended meta-analysis by Pearson et al showed not only significantly delayed fracture healing but also a higher frequency of non-unions after fracture, spinal fusion, osteotomy, or arthrodesis in smokers [7]. This finding is fostered by the retrospective study of Hess et al reporting a higher frequency of post-surgical tenderness, wrist stiffness, non-unions, and revision surgeries in smokers with distal radius fractures (when compared to non-smokers) [6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the majority of patients that receive surgical fixation for DRF have good to excellent outcomes, PD patients appear to have inferior results. In the general population, the nonunion rate is reported to be as low as < 1% and the overall complication rate in current literature for DRF ranges from 14 to 30% in the general population [4,[12][13][14]. In our study, we considered patients to have a treatment failure if there was loss of reduction, malunion or nonunion of fracture, or persistent pain at the injured site 6 months after surgery.…”
Section: The Outcome Of Fractures In Patients With Parkinson's Disease and Elderly Patientsmentioning
confidence: 99%
“…In the general population, the nonunion rate is reported to be as low as < 1% and the overall complication rate in current literature for DRF ranges from 14% to 30% in the general population. 4,[12][13][14] In our study, we considered patients to have a treatment failure if there was loss of reduction, malunion or nonunion of fracture, or persistent pain at the injured site 6 months after surgery. We noted 4.6% of the non-PD patients had treatment failure, while 39.1% of the patients in the PD group were considered to have treatment failure.…”
Section: The Outcome Of Fractures In Patients With Parkinson's Diseasmentioning
confidence: 99%